C. B. Tilanus. Input-output experiments : The Netherlands, 1948-1961. Rotterdam : Rotterdam University Press, 1966. 141 p. Economic Series. v. 5, 1966. 141 p - Peña S., Raúl de la (Estudios Demográficos y Urbanos, 1968)
C. B. TILANUS, Input-out put experiments: The Netherlands, 1948-1961. Rotterdam, Rotterdam University Press, Economic Seríes. Vol. 5, 1966.